2007
DOI: 10.1080/14786430701342172
|View full text |Cite
|
Sign up to set email alerts
|

Does In form In-rich clusters in InGaN quantum wells?

Abstract: International audienceThe reason the InGaN/GaN quantum well system emits intense light even though the dislocation density is high is assessed. It is concluded that In-rich clusters in InGaN quantum wells do not exist in the specimens we have studied, and in any case they are not necessary to localise the excitons and for bright light emission

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 34 publications
5
63
0
Order By: Relevance
“…Studies [36] have shown that InGaN is a random alloy in which indium atoms distribute randomly but uniformly, and that they do not form the so-called indium-rich islands of the nanometer-length scale especially when the indium fraction is as low as x = 15 % as in our case. In a disk-shaped In 0.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Studies [36] have shown that InGaN is a random alloy in which indium atoms distribute randomly but uniformly, and that they do not form the so-called indium-rich islands of the nanometer-length scale especially when the indium fraction is as low as x = 15 % as in our case. In a disk-shaped In 0.…”
mentioning
confidence: 89%
“…Such sharp diameter cut-off provides strong evidence that the formation of our QDs is not due to the random inclusion of so-called localization centers (LCs). Such LCs, expected to be a few nanometers large in the lateral dimension, [36] could form due to QW thickness fluctuations or at indium-rich islands. The sharp intensity cut-off at ∼ 15 nm clearly suggests that the emission intensity is correlated with the size of the entire InGaN disk rather than small few-nanometer-scale LCs within the InGaN disk.…”
mentioning
confidence: 99%
“…The reason that InGaN LEDs are much more tolerant of TDs than other conventional III-V materials is probably due to carrier localisation effects [20][21][22][23][24][25][26]. The first contributing factor is the monolayer height interface steps on the InGaN quantum wells.…”
Section: à2mentioning
confidence: 99%
“…Second, electronic structure calculations have predicted strong hole localization even in the absence of compositional inhomogeneities [6], with preferential localization along randomly formed [1,1,0] In-NIn-N-In chains [39]. Finally, InGaN QW width fluctuations (even as small as one monolayer) have been proposed as an effective mechanism to provide localization energies above kT at room temperature [31].…”
Section: Extended Defectsmentioning
confidence: 99%